(untitled) (Educational Knowledge, 2019)
The teaching of Natural Sciences represents a shift in the didactic model to improve traditional teaching processes and propose innovative activities that lead to experimentation and strengthen the connection between theory and practice. In response, the objective of this research was to incorporate Project-Based Learning (PBL) methodology into the use of the school garden as a pedagogical resource and the development of experimental practices in this ecological classroom, within the Science, Health, and Environment subject of the third cycle of basic education. The results obtained were satisfactory, as students achieved significant learning by constructing knowledge through direct practice with nature, contextualizing and integrating the conceptual content covered in class. Not only were their scientific competencies strengthened, but also their teamwork, solidarity, commitment, and service skills; interacting with their classmates and applying interdisciplinarity as a central focus in the processes of knowing how to do and knowing how to be within the context. The final product was a methodological guide that forms the basis of the work in the subject of Science, Health and Environment, allowing the integration of subjects such as: Mathematics, Language, Social Studies and English, achieving the integration of subjects within the garden, leaving a precedent of educational innovation within a complex school center, which houses a large student population of the Salvadoran educational system.